Retrospective Evaluation of Hemithyroidectomy in 14 Horses. Issue 7 (6th September 2016) - Troillet, Antonia; Böttcher, Denny; Brehm, Walter; Scharner, Doreen
Abstract : Objective: To describe the presentation, presurgical diagnostic findings, treatment, and outcome of horses with histologically confirmed, unilateral thyroid neoplasia. The complications, particularly laryngeal hemiplegia, were investigated. Study Design: Retrospective case series. Animals: Client‐owned horses (n=14). Methods: Medical records of horses presenting with a unilateral thyroid mass due to neoplasia from 2003–2015 were reviewed. Horses must have undergone preoperative clinical evaluations that included ultrasound examination of the mass and upper airway endoscopy. Short‐term follow‐up at 2 weeks after surgery and owner questionnaire for long‐term follow‐up at >6 months were completed. Results: Fourteen horses aged 6–21 years were included. The majority of tumors were adenocarcinomas (11/14), mainly diagnosed in mares (9/14). Intraoperative complications included hemorrhage (1/14) and postoperative complications included seroma formation (4/14). No horse developed postoperative laryngeal hemiplegia. No horses developed clinical signs of metastases or a thyroid disorder long term (mean follow‐up 4.9 years). All owners reported a successful long‐term outcome. Conclusion: The clinical findings of thyroid neoplasia in horses are not associated with the diagnosis of malignancy. Complete surgical resection of the abnormal lobe prevents local recurrence of neoplastic thyroid tissue. The modified hemihyroidectomy technique preserves the function of the recurrent laryngeal nerve.